2017
DOI: 10.1262/jrd.2016-124
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exosome-like vesicles on cumulus expansion in pigs <i>in vitro</i>

Abstract: Cell-secreted vesicles, such as exosomes, have recently been recognized as mediators of cell communication. A recent study in cattle showed the involvement of exosome-like vesicles in the control of cumulus expansion, a prerequisite process for normal ovulation; however, whether this is the case in other mammalian species is not known. Therefore, this study aimed to examine the presence of exosome-like vesicles in ovarian follicles and their effects on cumulus expansion in vitro in pigs. The presence of exosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 58 publications
0
46
0
1
Order By: Relevance
“…These pathways are involved in the regulation of ovarian functions, including folliculogenesis, luteogenesis, and steroidogenesis [1215]. The presence of exosome-like vesicles was also reported in follicular fluids of several other mammalian species, including human, bovine, and pig [1619]. The miRNA content in the exosome-like vesicles from human and bovine has been studied [16, 17], and these miRNAs are known to target signaling pathways similar to those targeted by equine vesicles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These pathways are involved in the regulation of ovarian functions, including folliculogenesis, luteogenesis, and steroidogenesis [1215]. The presence of exosome-like vesicles was also reported in follicular fluids of several other mammalian species, including human, bovine, and pig [1619]. The miRNA content in the exosome-like vesicles from human and bovine has been studied [16, 17], and these miRNAs are known to target signaling pathways similar to those targeted by equine vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, in the present study, we evaluated the characteristics of transcriptomic profile of mRNA content in exosome-like vesicles from ovarian follicles using pig as a model. The presence of the exosome-like vesicles in porcine follicular fluid (pFF) has been previously reported [19]. As mural granulosa cells (MGCs) are one of the most abundant cell types in ovarian follicles, the transcriptomic profile of the MGCs was also investigated to test whether MGCs are the main producers of the follicular exosome-like vesicles.…”
Section: Introductionmentioning
confidence: 99%
“…The normal expansion of COC is required for ovulation, which requires the abundant expression of transcripts, such as COX2, PTX3, CD44, TNFAIP6, and HAS2 ( 31 ). Moreover, variations in the ECM secreted from cumulus cells are also essential for oocyte release.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent years, several studies have revealed that exosomes could be released from various parts of the female reproductive tract, including uterine, oviducts epithelium, endometrium, as well as preimplantation embryos, the placenta trophoblastic cells . It is mentioned that exosomes play a substantial role in transmitting specific cargo molecules in the reproductive tract to modulate transcription and translational activity, granulosa cells proliferation and differentiation, cumulus expansion, gametogenesis, normal follicular growth, oocyte maturation, fertilization rate, embryo development, blastocyst formation and implantation, in pregnancy outcome and fertility .…”
Section: The Role Of Extracellular Vesicles In Female Physiological Pmentioning
confidence: 99%